Prospective surveillance for invasive Staphylococcus aureus and group A Streptococcus infections in a setting with high community burden of scabies and impetigo. (July 2021) - Thean, Li Jun; Jenney, Adam; Engelman, Daniel; Romani, Lucia; Wand, Handan; Mani, Jyotishna; Paka, Jessica; Cua, Tuliana; Taole, Sera; Soqo, Vika; Sahukhan, Aalisha; Kama, Mike; et al.
Highlights: Fiji has high incidence rates of invasive group A streptococcal infections and Staphylococcus aureus infections. Case fatality for invasive S. aureus and group A streptococcal infections was high. Skin infections were the most common clinical foci for both invasive S. aureus and group A Streptococcus. Abstract: Background: Invasive Staphylococcus aureus (iSA) and group A Streptococcus (iGAS) impose significant health burdens globally. Both bacteria commonly cause skin and soft tissue infections (SSTIs), which can result in invasive disease. Understanding of the incidence of iSA and iGAS remains limited in settings with a high SSTI burden. Methods: Prospective surveillance for admissions with iSA or iGAS was conducted at the referral hospital in Fiji's Northern Division over 48 weeks between July 2018 and June 2019. Results: There were 55 admissions for iSA and 15 admissions for iGAS (incidence 45.2 and 12.3 per 100, 000 person-years, respectively). The highest incidence was found in patients aged ≥65 years (59.6 per 100, 000 person-years for iSA and iGAS). The incidence of iSA was higher in indigenous Fijians (iTaukei) (71.1 per 100, 000 person-years) compared with other ethnicities (incidence rate ratio 9.7, 95% confidence interval 3.5–36.9). SSTIs were found in the majority of cases of iSA (75%) and iGAS (53.3%). Thirteen of the 14 iGAS strains isolated belonged to emm cluster D ( n = 5) or E ( n = 8). The case fatality rate was high for both iSA (10.9%) and iGAS (33.3%). Conclusions: The incidence of iSA and iGAS in Fiji is very high. SSTIs are common clinical foci for both iSA and iGAS. Both iSA and iGAS carry a substantial risk of death. Improved control strategies are needed to reduce the burden of iSA and iGAS in Fiji.